Inclusivity in Higher Education: Ethnic Differences in Post-secondary Educational Pathways - R. Vicky Maldonado (Canadian Society for Studies in Education, 2010)
Ethnic group differences in educational attainment at the post-secondary level are evident in Canada and the United States. The factors contributing to the lack of inclusivity in higher education are complex. This paper explores outcomes and mechanisms of educational stratification by providing an overview of structural and cultural explanations of educational disparities. Assimilation, segmented assimilation and blocked mobility theories are explored first, followed by socioeconomic origins, social capital resources, skill deficits, aspirations, and oppositional culture theories. This paper argues that the educational landscape is indeed an uneven one for immigrants and their families, particularly when belonging to an ethnic minority group.